Kemampuan Translasi Antar Representasi Matematika Siswa dalam Memecahkan Masalah SPLDV Ditinjau dari Kemampuan Matematika - Awi; Nasrullah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This research aim to analyze translation of visual representation to verbal representation in solving two variable system of linear equation topic. three students of grade IX-A were selected as subject in term of result mathematic test. The problem solving process carried out by students based on Polya four stages. problem solving test like SPLDV was given to subject then interview related to test.The result shows that subject with high mathematic ability pass all translational indicators between representations for each given problem. subject with medium mathematic ability only pass all translational indicators between representations for one given problem. subject with low mathematic ability not pass all translational indicators between representations .